Human Growth and Growth Hormone: From Antiquity to the Recominant Age to the Future - Graber, Evan; Reiter, Edward O.; Rogol, Alan D. (Frontiers in Endocrinology, 2021)
Since antiquity Man has been fascinated by the variations in human (and animal) growth. Stories and art abound about giants and little people. Modern genetics have solved some of etiologies at both extremes of growth. Serious study began with the pathophysiology of acromegaly followed by early attempts at treatment culminating in modern endoscopic surgery and multiple pharmacologic agents. Virtually at the same time experiments with the removal of the pituitary from laboratory animals noted the slowing or stopping of linear growth and then over a few decades the extraction and purification of a protein within the anterior pituitary that restored, partially or in full, the animal's growth. Human growth hormone was purified decades after those from large animals and it was noted that it was species specific, that is, only primate growth hormone was metabolically active in primates. That was quite unlike the beef and pork insulins which revolutionized the care of children with diabetes mellitus. A number of studies included mild enzymatic digestion of beef growth hormone to determine if those "cores" had biologic activity in primates and man. Tantalizing data showed minimal but variable metabolic efficacy leading to the "active core" hypothesis, for these smaller peptides would be amenable to peptide synthesis in the time before recombinant DNA. Recombinant DNA changed the landscape remarkably promising nearly unlimited quantities of metabolically active hormone. Eight indications for therapeutic use have been approved by the Food and Drug Administration and a large number of clinical trials have been undertaken in multiple other conditions for which short stature in childhood is a sign. The future predicts other clinical indications for growth hormone therapy (and perhaps other components of the GH?IGF-1 axis), longer-acting analogues and perhaps a more physiologic method of administration as virtually all methods at present are far from physiologic.